Evaluation of Fruit Quality Characteristics in ‘Irwin’ Mango Grown via Forcing Cultivation in a Plastic Facility - Wijethunga, W.M. Upeksha Darshani; Shin, Mi Hee; Jayasooriya, L. Sugandhi Hirushika; Kim, Gyeong Ho; Park, Kyoung Mi; Cheon, Mi Geon; Choi, Sang Woo; Kim, Hong Lim; Kim, Jin Gook (Weon'ye gwahag gi'sulji, 2023)
The ‘Irwin’ mango is one of the most popular mango cultivars in South Korea, but the fruit perishes quickly after harvesting. Identifying the fruit characteristics is essential to improve the quality after harvest because they vary with the maturity stage. In this study, ‘Irwin’ mango samples were harvested as a whole and divided into five distinct maturity stage groups depending on the green color proportion of the total fruit skin (S1: Green > 50%, S2: Green 30–50%, S3: Green 20–30%, S4: Green 10–20%, S5: Green 0%). The physicochemical properties, in this case the chromaticity, firmness, soluble solids content (SSC), titratable acidity (TA), ethylene production rate, and respiration rate, were measured soon after harvesting the fruit. Consequently, the S1 and S5 stages showed higher and lower firmness and TA levels, respectively. Moreover, these values were significantly different in each stage. Along with the maturity stage, highest and lowest values in SSC were observed in S5 and S1; correspondingly, and the highest carbon dioxide and ethylene concentrations were observed in stages S5 and S4. With regard to chromaticity, no apparent variations were observed between the front and back sides of the fruit at every color value, though there were significant differences among the stages. By observing all of these quality characteristics, it can be concluded that fruit at the S3 and S4 stages are suitable for storage and are less preferred by consumers at harvest. In this case, the S5 stage is most suitable because the mangoes are at the ready-to-eat stage, more preferred by consumers, and can also be marketed at a higher price KCI Citation Count: 2